Uso de smartphones e telas por estudantes de ensino médio e sua relação com o desempenho acadêmico - Villas Boas, Glauco Keller (Universidade Federal de São Carlos, 2026)
Considering that social media and communication apps have been increasingly used by adolescents, and that the use of smartphones and screens, both inside and outside the classroom, is a current reality, this research aims to assess whether the use of smartphones and screens by high school students has any influence on their academic performance in language subjects (grammar, literature, and writing). As specific objectives, it seeks to identify the frequency of smartphone and general screen use among high school students and to analyze their academic performance in language assessments before and after Law No. 15,100 of January 13, 2025. The research draws on the theoretical concepts of experience and semi-formation developed, respectively, by critical theorists Walter Benjamin and Theodor W. Adorno, and also engages with the concept of hominization proposed by Christoph Türcke.To address the research objectives, 100 students from a private school in a medium-sized city in the state of São Paulo answered an online questionnaire designed by the researcher. The instrument included a characterization survey, open and closed questions about smartphone and screen use, and an adapted version of the Internet Addiction Test (IAT). Quantitative data were analyzed using descriptive and inferential statistics (correlation, mean comparison) through the software JASP version 0.18.3.0, while qualitative data were examined through content analysis. The results indicated that all participants owned smartphones and acknowledged that their frequency of use was high, with some reporting that their parents had asked them to reduce it. It was found that smartphone use occurred more frequently for recreational purposes and that, in the classroom, it was commonly associated with checking messages during moments of tiredness or “having nothing to do.” Most participants (77%) showed scores indicating controlled use, while 23% presented signs of occasional or frequent problems. Regarding the perception of effects on mental health, reports of anxiety were observed. When correlating smartphone use with students’ grades in language subjects, significant but weak negative correlations were found between smartphone use and writing grades, indicating that the higher the scores on the subscales, the lower the writing grades. There were statistically significant differences in the grades obtained in the subjects in 2024 and 2025, with a decline in performance observed in all subjects evaluated. Some limitations and potential of the research are discussed, highlighting the role of adolescents, the difficulties in evaluating academic performance, and the repercussions of smartphone use on human and social development.
Use of smartphones and screens by high school students and its relationship with academic performance
Keywords: Teoria crítica; Smartphones; Ensino médio; Desempenho acadêmico; Linguagem; Critical theory; High school; Academic performance; language; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade